Flood Propogation - Pandey, Bharat Raj (Journal of Advanced College of Engineering and Management, 2023)
The catastrophic failure of the dam creates to a rapid changes of flow depth which causes a devastating damage in the cultivated land in the downstream of the dam. The precise calculation to its attenuation of the wave height is critical to the design of the protection work for the cultivated land of the downstream communities. Therefore, this topic is aimed to present an illustration the estimation of the open channel surges in the downstream river reaches.